The Relationship between Spiritual Intelligence and the Risk of Depression in Postpartum Mothers - Atika, Suci Dwi; Elita, Veny; Tampubolon, Nurhannifah Risky (CV. Rayyan Dwi Bharata, 2024)
Introduction: Postpartum depression is a mood disorder that occurs after giving birth, which can be dangerous if ignored. One effort that is considered capable of preventing depression is spiritual intelligence. This study aims to determine the relationship between spiritual intelligence and the risk of depression in postpartum mothers. Method: This research is a quantitative study using a descriptive correlation design with a cross-sectional approach. The research sample was 83 postpartum mothers taken based on inclusion criteria using purposive sampling technique. The instruments in this study used the Edinburgh Postnatal Depression Scale (EPDS) questionnaire and The Spiritual Intelligence Self-Report Inventory (SISRI) which had been tested for validity. The analysis used is the chi-square test analysis. Results: Of the 83 respondents, (15.7%) had low spiritual intelligence, (33.7%) had medium spiritual intelligence, and (50.6%) had high spiritual intelligence. Then (28.9%) were at risk of depression and (71.1%) were not at risk of depression. The results of the Chi-square test analysis show that there is a significant relationship between spiritual intelligence and the risk of depression in postpartum mothers with p-value = 0.000 a (0.1). Conclusion: Spiritual intelligence and the risk of depression in postpartum mothers have a significant relationship. The higher the spiritual intelligence, the lower the risk of experiencing postpartum depression. Recommendation: Postpartum mothers are expected to increase their approach to religion so that they are better able to accept the problems that occur after giving birth, both psychological and physical, so that the risk of depression can be prevented.